2022
DOI: 10.24843/eja.2022.v32.i04.p07
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Mempengaruhi Tax Aggressiveness: Bagaimana Pengaruh Board Gender Diversity?

Abstract: This study aims to analyze the effect of audit quality, size of the board of directors, and capital intensity on tax aggressiveness with gender diversity of directors as a moderating variable. The research was conducted on mining companies based on the IDX-IC classification on the IDX for 4 years, 2016-2019 period. The sample obtained was 47 observations with cross-sectional data method and multiple linear regression test. The results show that audit quality is negatively related to tax aggressiveness, capital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Furthermore, Riguen et al (2020) showed that boards of directors with female directors could demand more from their auditors and choose the best ones. The results revealed by Anggelina et al (2022), who indicate that companies with higher levels of gender diversity on their board of directors emphasize the connection between audit quality and tax avoidance. Therefore, the audit quality will also be improved if there are more women on the board of directors for the organization.…”
Section: The Influence Of Board Gender Diversity In Moderating Relati...mentioning
confidence: 99%
“…Furthermore, Riguen et al (2020) showed that boards of directors with female directors could demand more from their auditors and choose the best ones. The results revealed by Anggelina et al (2022), who indicate that companies with higher levels of gender diversity on their board of directors emphasize the connection between audit quality and tax avoidance. Therefore, the audit quality will also be improved if there are more women on the board of directors for the organization.…”
Section: The Influence Of Board Gender Diversity In Moderating Relati...mentioning
confidence: 99%
“…Adanya direksi wanita yang lebih tinggi dan cenderung menuntut kualitas audit yang lebih tinggi, mereka bersedia membayar biaya audit yang lebih tinggi pula serta lebih cenderung memilih auditor spesialis dibandingkan dengan rekan-rekan mereka pada jajaran dewan. Keberadaan wanita dalam jajaran dewan direksi akan menuntut kualitas audit yang lebih tinggi(Angelina et al, 2022).…”
unclassified